The Algerian administrative judiciary's specificity through the constitutional modification of the year 2020 - Kikaya, Moufida (Journal of Human Sciences, 2025)
The administrative dispute has enjoyed a specificity since its adoption the administrative chambers system between the apparently unified judicial system and the practically dual judicial system, and the Algerian administrative judicial system's specificity was actually established by the constitutional modification of the year 1996 that established the state's council as an evaluated body of the administrative judiciary bodies' works, where it exercises a judicial function as well as undertakes an advisory function as a privilege which sets the most outstanding characteristics of the administrative judicial system whose structures were gradually formed starting with the establishment of administrative courts under the law no: 98-02, to be completed by the establishment of administrative courts of appeal under the constitutional modification of the year 2020.